48.6k views
2 votes
Rearrange the formula s = vt + 16t2 for v.

User Seasick
by
5.8k points

2 Answers

5 votes
For this case we have the following equation:
s = vt + 16t2
Rewriting we have:
vt = s - 16t2
Clearing v we have:
v = s / t - 16t
Answer:
The equation rewritten for v is given by:
v = s / t - 16t
User Cerebrate
by
6.3k points
7 votes
We have to make v the subject of the formula. The steps to solve this problem are listed below:


s=vt + 16t^(2) \\ \\ s-16t^(2) =vt \\ \\ v= (s-16t^(2) )/(t)

The above formula shows v isolated on one side of the equation and all other variables on the other side.
User A Junior
by
5.8k points